National champion versus foreign takeover - Jens Südekum (Institute for the Study of Labor (IZA), 2007)
We analyze an oligopolistic market where a domestic and a foreign firm are engaged in a takeover battle for a domestic competitor. Any merger or acquisition (M&A) must be approved by a welfare maximizing domestic competition agency which may or may not be prone to economic patriotism. A patriotic government does not (fully) count wealth of domestic shareholders as relevant producer surplus if this wealth has been generated by selling a domestic firm abroad. We show that globalization (decreasing transport costs) has a different impact on the equilibrium ownership structure of that industry, depending on the type of government. With an unbiased competition agency we find that the foreign takeover is more likely to occur the higher the level of trade openness is. However, when the domestic government is biased we find that globalization reinforces the case for promoting national champions. This may explain why some countries have recently spent considerable effort to deter foreign attempts to acquire domestic firms.
Keywords: 330; Übernahme; Ausländisch; Multinationales Unternehmen; Wettbewerbspolitik; Public Choice; Nationalismus; Politik der offenen Tür; Oligopol; Theorie